Stability of Cubic Functional Equation in Random Normed Space - Pinelas, Sandra; Govindan, V.; Tamilvanan, K. (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, we present the Hyers-Ulam stability of Cubic functional equation. where n is greater than or equal to 4, in Random Normed Space.